Investigating the adversity quotient: Assessing elementary school students’ proficiency in solving two-dimensional problems - Dyah Worowirastri Ekowati; Agung Dediliawan Ismail; Erna Yayuk; Beti Istanti Suwandayani; Alfiani Athma Putri Rosyadi; Minatun Nadlifah (Universitas Muhammadiyah Malang, 2024)
The Adversity Quotient (AQ) is a measure of a person's resilience in adversity and ability to solve problems in Mathematics. In this study, the solution to the two-dimensional shape problem of grade 3 elementary school students was explained based on the adversity quotient. This type of descriptive exploration is used to conduct qualitative research. Three grade III students of SD Muhammadiyah 9 Malang City were involved in this study representing 3 categories of AQ. The tools used are written exam questions, interview guidelines, and observations. One question related to the circumference of a two-dimensional shape is given in the form of a written test. This study analyzed the learning outcomes of three third-grade students through four stages: data transcription, data selection, data presentation, and drawing conclusions. The results showed two problem-solving patterns based on the AQ category. The first pattern is understanding the problem, planning the problem-solving, executing the plan, and looking back is done by the category of quitters and campers. The second pattern of understanding the problem, planning the problem solving, executing the plan, understanding the problem, planning the problem solving, executing the plan, and looking back is done with the category of climbers.